Pengaruh Maqashid Syariah terhadap Kebahagiaan Muslimah di Indonesia: Studi Kasus Ifls 5 Tahun 2014 - Fella Rifnawati; Alifia Epriyani (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the effect of maqashid sharia on Muslim women's happiness in Indonesia, using data from the Indonesian Family Life Survey (IFLS) 5th wave 2014. Maqashid sharia, as a core concept in Islamic law, focuses on the maintenance of five main aspects, namely religion (ad-din), soul (an-nafs), intellect (al-aql), offspring (an-nasl), and property (al-mal). This study examines whether the implementation of maqashid sharia principles coupled with region of residence as a control variable has a significant impact on the subjective happiness of Muslim women in Indonesia. Using logit regression method and STATA software, this study found that the maintenance of health (soul), education (mind), and income (wealth) has a significant positive effect on Muslimah's happiness, heredity (lineage) shows an insignificant negative effect, religiosity (religion) shows a positive and significant relationship, while the region of residence has an insignificant negative relationship with the level of happiness of Muslimah in Indonesia. These results indicate that the subjective happiness of Indonesian Muslim women is more influenced by material dimensions than philosophical or spiritual matters. This research is expected to contribute to the formulation of public policies that support the social welfare of Muslimahs based on maqashid sharia.